Remarks by World Bank Group President David Malpass on Bretton Woods 75th Anniversary - Malpass, David (World Bank, Washington, DC, 2019)
David Malpass, President of the World Bank Group, commemorated the 75th anniversary of the 1944 conference held in Bretton Woods, New Hampshire which led to the creation of the World Bank. He spoke about key historical events and development challenges. He discussed the IDA19 replenishment and its importance to the Sahel. He noted the evolution of development policy and development finance, including highlights like the debt crisis, globally traded bonds, and Green Bonds. He mentioned advisory services and key reports produced by the Group.